Structural Performance of Grouted Sleeve Connectors with and without Transverse Reinforcement for Precast Concrete Structure - Aizat, Alias; Mohammad Amirulkhairi, Zubir; Khairul Anuar, Shahid; Ahmad Baharuddin, Abdul Rahman (Elsevier Ltd, 2013)
This paper presents the performance of the proposed grouted sleeve connector with and without steel spiral as transverse reinforcement under incremental tensile load until failure. The connector utilized mild steel pipe as sleeve where the sleeve consists of external and internal sleeve with the diameter of the external sleeve is larger than internal sleeve. The mild steel pipe and the steel spiral are used to confine and reinforce the grout and the two discontinued bars spliced end-to-end configuration in the sleeve. The test shows that, there are two modes of failure which were bar slipped and bar fractured outside the sleeve. Eleven specimens out of fourteen shows satisfactory results as it failed due to bar fractured outside the sleeve and achieve satisfactory ultimate tensile capacity. The stiffness and the ductility of the connectors also satisfy. Grouted sleeve connectors with steel spiral perform better compared to connectors without a steel spiral. The test shows that the performance of the grouted sleeve connector with or without steel spiral was governed by grout-bar bond, anchorage length and confinement action provided by the sleeve and the steel spiral. The connectors have a potential to be used in connecting precast concrete structure.